OP0200 Global DNA Methylation Patterns Differ Between Responders and Non-Responders in Psoriatic Arthritis Patients Treated with Tumor Necrosis Factor-α Inhibitors. (9th June 2015) - O'Rielly, D.D.; Zhang, Y.; Codner, D.; Dohey, A.; Zhou, A.; Al Ghanim, N.; Hamilton, S.; Zhai, G.; Rahman, P.
Abstract : Background: Although tumor necrosis factor-α inhibitors TNFi are well established treatment for psoriatic arthritis (PsA), the efficacy can vary greatly between patients. In this study, we examined the genome-wide epigenetic changes among TNFi responders and TNFi secondary failures in PsA patients Methods: Twenty-one PsA patients (15 males; 6 females) were considered TNFi responders of which 13 were treated with etanercept and 8 with adalumimab. The median follow up duration was 18 months. Twenty patients (5 males; 15 females) were secondary TNFi failures of which 15 were treated with etanercept and 5 with adalumimab. The median follow up duration was 36 months. Genome-wide DNA methylation profiling was performed using the Illumina HumanMethylation450k Beadchip, which measures ∼480, 000 different CpG sites per sample and covers 96% of RefSeq genes. The methylation level at each CpG site was measured by β values varying from 0 (no methylation) to 1 (100% methylation). Analysis was performed using a t-test after a Bonferroni-Holm correction was applied. Regions of interest were selected based on β value (β diff>5%) and p-value (p<0.01). Results: After quality control filtering, 384, 599 and 368, 863 CpG sites were evaluated for TNFi responders and TNFi failures, respectively. Analysis revealed 72 and 91 CpG sites of interest in the TNFi responder group and in the TNFi failure group, respectively. Top gene candidates for TNFi responders included TRAPPC9 (β diff=0.056; p=3.42x10 -6 - functions as an activator of NFkB); CCR6 (β diff=0.053; p=0.0028 - regulates the migration and recruitment of dentritic and T cells); and PSORSC13 (β diff=0.035; p=0.003). Top candidate genes for TNFi secondary failures included CD70 (encoded protein is a ligand for TNFRSF27/CD27), and TNFRSF1B (a member of the TNF receptor superfamily, that mediates most of the metabolic effects of TNFα). Conclusions: These preliminary results demonstrate that the global DNA methylation pattern differs between TNFi responders and secondary failures. They also serve to highlight the possible importance of epigenetic (methylation) changes with respect to the TNFα signaling pathway. High priority candidate regions and genes identified in this study warrant further validation. Disclosure of Interest: None declared